(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aimed to determine the effectiveness of multi-level marketing and to help them with the help of proposed intervention and remediation. Furthermore, results showed that income and incentives are effective in multi-level marketing as perceived by the respondent, and with the help of proposed intervention or remediation, It lessens the challenges encountered by the consumers. This study recommended that they need to first know their location signal to prevent an issue on the internet, and they also need to be aware of scammers. To make sure that the company is legitimate, you need to conduct a background check.